Assessment of knowledge, attitude and practice of diabetic people in Najran, Kingdom of Saudi Arabia - Babikr, Walid G.; Aedh, Abdullah I.; Ahmed, Awad Mohamed; Abdelraheem, Ahmed; Alasmary, Mohammed; Elhussein, Amar B.; Alijla, Anas R.; Ahmed, Mutaz M.; Assiri, Ali M.; Al-Qahtani, Awad M.; Younis, Abubaker A.; Alshehri, Hamdan; et al. (International Journal of Research in Medical Sciences, 2017)
Background: This cross-sectional hospital based study aimed at determining the level of knowledge, attitude and practice of diabetes among local people of Najran, Saudi Arabia. Methods: We aimed to investigate the levels of knowledge, attitude and practice among diabetic people in Najran area. Results: 10% of the participants scored >7, 28% scored >5 and 62% scored 5 and less in Knowledge questionnaire. None [0.00%] of the participants scored 7 or more out of the attitude questionnaire. 100% of the participants scored 5 and less out of 12. 100% of the participants scored >6 and 0% scored 12 or more in the practice questionnaire. Conclusions: Our study revealed that the level of knowledge, attitude and practice of diabetes in the area of Najran is very poor. We suggest that a structured educational program to be adopted by the health authorities in Saudi Arabia.